Convenção de arbitragem – novas perspectivas sobre o estudo da cláusula compromissória cheia e vazia e o termo de compromisso arbitral - Paula, Ludmila Cruvinel Gordo de (2010)
Arbitrtion has increased its scope in contemporary societies, but is still underused, despite the Express constitutional authorization. In fact, alternative methods of conflict resolution is a new field of procedures, which are replacing traditional ways of solving problems related to disputes of rights available. The increase in economic transactions has changed the way of understanding the traditional theory of legal transactions, in which a contract is not concluded by the same, but there is a huge difference in the legal position of the parties. The solution demands for arbitration is based on the autonomy of the will of the parties, to provide justice faster, faster, and cheaper in Brazil. For this method to be effective, necessary it is that the convention is held and developed without vices will. The dissertation it is the validity of the arbitration agreement, recognizing, however, that there are several points to be reformed, with respect to special legislation. Thus, on account of such facts, this study will investigate the phenomena of historical facts related to arbitration, until our present day, with emphasis on the advantages of the institute, and shape and effectiveness of the arbitration agreement.